Soulbound Tokens: Enabler for Privacy-Aware and Decentralized Authentication Mechanism in Medical Data Storage - Biagio Boi; Franco Cirillo; Marco De Santis; Christian Esposito (Blockchain in Healthcare Today)
Context: The digitalization of the healthcare sector faces significant challenges due to the diverse representation of data and their distribution across various hospitals. Moreover, security is a key concern as healthcare-related data are subject to the legal obligations of GDPR and similar data protection legislations. Standardization efforts like HL7 have been implemented to enhance data interoperability. However, authentication still remains a critical issue, even significant challenges.